Perubahan Esensi Ragam Hias “Sepak Bola” pada Batik Masa Kini - Michael HB Raditya (Journal of Contemporary Indonesian Art, 2015)
The Essence’s Transformation of “Football” Decoration of Batik Today. Nowadays, batik has a massive development in its existance. In primary side, the existance more strong, but in other side batik had been changed. About Two years ago, Batik football decorative emerged and become a commodity by the batik artisans. The position of batik footbal decorative has become a dilemma. The issues made because there are many support and counter for that development. The issue about aesthetics and commoditization was creating by purpose of this change. Moreover, questioning the essence and existance of batik itself. In this article, batik football decorative will be discussed based on the essence and change. The dicussion about essence will be analyze with the aesthetic and commoditization perspective, while the changes would be discussed with the function and change itself. This thing did it to find the essence of batik football decorative. Conclusion of the research said the batik football decorative used a commoditization and decrease the aesthetic things to create the batik itself. The change occurs because there is a correlation between internal and external aspect on integrated of batik. The Analyze becomes a reflection to society, in batik for spesific, and arts in general view.Keywords: Batik, Football, Transformation, Commoditization, Essence